Obesity and COVID-19 in the octogenarians. (14th October 2021) - Scarpone, M; Bergami, M; Cenko, M; Bugiardini, R; Manfrini, O
Abstract: Background: Obesity has been identified as the comorbidity more frequently associated with severe forms of COVID19. As the very elderly subjects are particularly prone to severe forms of the disease, but are less affected by obesity we specifically addressed the question on the influence of age on the relationship between BMI and COVID19 prognosis. Purpose: To assess the relationship between obesity and early COVID-19 prognosis in octogenarians patients. Methods: Patients were determined to have COVID-19 if they had a positive SARS-CoV-19 swab. We used logistic regression analyses to control for confounding by concomitant risk factors. Clinical characteristics and COVID-19 related outcomes (i.e. invasive mechanical ventilation [IMV], death and discharge by day 7 [D7]) were analyzed according to BMI status and age (older vs younger than 80 years). Results: Among 601 patients with COVID-19 confirmed disease there 514 (85.5%) normal weight and 87 (14.5%) obese subjects (BMI >30 kg/m 2 ). In a multivariable adjusted model, the primary outcome (IMV and/or death by D7) was significantly associated with obesity in the overall population (OR 2.19; 95% CI: 1.26–3.8). After multivariable adjustment, primary outcome by D7 was significantly associated with obesity in patients aged younger than 80 years (OR 2.54; 95% CI: 1.38–4.68), while such an association was no longer found in those aged 80 years and older (OR 0.42; 95% CI: 0.05–3.33). Conclusions: Obesity is associated with poor early prognosis in patients with confirmed COVID19 disease. The deleterious impact of obesity on COVID-19 prognosis is no longer observed in the elderly aged 80 years and older. Very advanced age by itself must be considered as a major risk for severe COVID-19 outcomes in all people irrespective of BMI status. Funding Acknowledgement: Type of funding sources: None.